Hawkers on hygiene: a comprehension towards a safety and hygiene food preparation among local hawkers in Gombak Zone, Selangor/ Nurul Iwani Muzaili and Anis Shaakirah Mohd Zainuri - Muzaili, Nurul Iwani; Mohd Zainuri, Anis Shaakirah (2021)
Hawkers are titles for individuals involved in street food. They are among the contributors to the increase of foodbome illness cases in Malaysia and globally. This is due to the lack of food safety and hygiene during food handling. Therefore, this study aims to identify the level of food safety and hygiene in preparing food among hawkers in the Gombak zone. Knowledge, Attitude and Practise (KAP) model used as a guideline to meet the objectives. A cross-sectional study was conducted among hawkers in the Gombak zone, Selangor. A total of 260 respondents were selected by using cluster sampling. Data were collected through a self-administered questionnaire which consisted of four sections which are socio-demographic characteristics, knowledge, attitudes, and practices. After all data of questionnaires complete, the data were analysed using Statistical Package for the Social Science (SPSS) 27.0.1.0 version. The results showed that the mean score percentage of knowledge is poor (47.4%) while attitudes (69.5%) and practices (57.7%) are categorized as average levels based on the KAP model. The finding of this study served as an eye-opener for hawkers to follow a regulation set by the government and be responsible for preparing hygienic food. This study also may help the Local Health Authority to identify KAP level among hawkers in the Gombak zone and took an action for improvement of KAP among them.